The Effects of Climate Change Scenarios on Carpinus betulus and Carpinus orientalis in Europe - Varol, Tugrul; Cetin, Mehmet; Ozel, Halil Baris; Sevik, Hakan; Zeren Cetin, Ilknur (Springer Science and Business Media LLC, 2022)
Occurring mainly as a result of human activities, global climate change is considered the most important problem of the current years. It was stated that global climate change will directly or indirectly influence the entire organic life on earth and that the group which will be affected by this process at most will be the plants, which have a limited migration mechanism, and especially the forests. In order to protect from the destructive effects of this process, it is important to determine the possible effects of climate change and to take measures addressing the future effects. Within the scope of this study, it was aimed to determine how the appropriate distribution areas of Carpinus betulus and Carpinus orientalis species widely spreading the European continent will be affected by the process of global climate change. In this parallel, by employing 15 bioclimatic variables by the RCP (Representative Concentration Pathway) 4.5 and RCP 8.5 global climate scenarios from the WorldClim database, Maximum Entropy software was used in modeling the years 2040, 2060, 2080, and 2100 and the changes in appropriate distribution areas of these species were calculated in units of area and percentage. As a result of the study, it was determined that the population loss might exceed beyond 25% at the altitudes below 1600 m for Carpinus betulus and beyond 30% at the altitudes below 1000 m for Carpinus orientalis, that the appropriate distribution areas will expand at higher altitudes, and that this increase may be more than 100% at the altitudes of 1000-2000 m for Carpinus orientalis. However, it is projected that the species will not be able to migrate to the newly emerging appropriate distribution areas fast enough and, moreover, significant population losses may occur for this reason. Republic of Turkey Ministry of Agriculture and Forestry, General Directorate of Forest Engineering The authors thank the support by the Republic of Turkey Ministry of Agriculture and Forestry, General Directorate of Forest Engineering, and the General Directorate of Meteorology for their prompt responses to our requests.
Keywords: Climate Change; Rcp Scenarios; Carpinus Orientalis; Pollution; Carpinus Betulus